Aging of the composite material in different environments - BOUBEKEUR, Bahia (Biopolymer Applications Journal, 2025)
The present work concerns the study of aging a new biodegradable material by mixing the poly lactic acid (PLA), thermoplastic biodegradable, with a low density in the presence of compatibilist PE-GMA in a different environment. The sample formulations LDPE/PLA/PE-GMA (20/80/5; 0/100/0; 100/0/0) are tested in soil and water over time. The aged samples are characterized (by mass loss, pH, and infrared spectroscopy). The results show that the mass loss of blend LDPE/PLA/PE-GMA is 24% after 5 weeks in water at 60°C. The pH value decreases over time. A negligible amount of mass loss in the soil is observed with a pH of 5 and ambient temperature. All results are confirmed by analysis of Infrared Spectroscopy